Evidence of recent treeline dynamics in southwest Yukon from aerial photographs - Danby, R.K.; Hik, D.S. (2007)
Small-scale vertical aerial photographs taken in 1947 and 1948 covering 200 km2 of the Kluane Ranges, southwest Yukon, were compared with corresponding photographs taken in 1989 for the purpose of characterizing changes in the distribution and abundance of white spruce (Picea glauca (Moench) Voss) at the alpine treeline. Digital photogrammetry, including orthorectification and on-screen interpretation, was supplemented by stereoscopic inspection of the original prints. Qualitative assessment of change across nine image pairs was accompanied by quantitative analysis of changes in spruce density and elevation using 1 hectare plots and 100 m wide elevational belt transects, respectively, superimposed on the orthorectified images. Significant changes were observed over the 41 years, but the degree of change varied throughout the study area. The most common changes were an increase in canopy size of individual trees and an increase in stand density resulting from the establishment of new individuals. Several instances of treeline advance were also observed. An absence of major natural disturbances or widespread land use change indicates that treeline change is attributable to climate. Results from concurrent dendroecological studies indicate that these dynamics represent only part of the total extent of change to occur during the 20th century.